Non-Discharge Methods for Partial Water Softening Using Zeolite Process with Discharge Reagentless Utilization - G. K. Feyziyev; G. G. Guseynova; R. T. Ismayilov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers developed technological schemes of non-discharge methods of partial  water softening using zeolite process with discharge reagentless utilization. Various versions of technological schemes of partial water softening are proposed in the paper.